Nanoliposomal irinotecan with fluorouracil and folinic acid in metastatic pancreatic cancer after previous gemcitabine-based therapy (NAPOLI-1): a global, randomised, open-label, phase 3 trial. Issue 10018 (6th February 2016) - Wang-Gillam, Andrea; Li, Chung-Pin; Bodoky, György; Dean, Andrew; Shan, Yan-Shen; Jameson, Gayle; Macarulla, Teresa; Lee, Kyung-Hun; Cunningham, David; Blanc, Jean F; Hubner, Richard A; Chiu, Chang-Fang; et al.
Summary: Background: Nanoliposomal irinotecan showed activity in a phase 2 study in patients with metastatic pancreatic ductal adenocarcinoma previously treated with gemcitabine-based therapies. We assessed the effect of nanoliposomal irinotecan alone or combined with fluorouracil and folinic acid in a phase 3 trial in this population. Methods: We did a global, phase 3, randomised, open-label trial at 76 sites in 14 countries. Eligible patients with metastatic pancreatic ductal adenocarcinoma previously treated with gemcitabine-based therapy were randomly assigned (1:1) using an interactive web response system at a central location to receive either nanoliposomal irinotecan monotherapy (120 mg/m 2 every 3 weeks, equivalent to 100 mg/m 2 of irinotecan base) or fluorouracil and folinic acid. A third arm consisting of nanoliposomal irinotecan (80 mg/m 2, equivalent to 70 mg/m 2 of irinotecan base) with fluorouracil and folinic acid every 2 weeks was added later (1:1:1), in a protocol amendment. Randomisation was stratified by baseline albumin, Karnofsky performance status, and ethnic origin. Treatment was continued until disease progression or intolerable toxic effects. The primary endpoint was overall survival, assessed in the intention-to-treat population. The primary analysis was planned after 305 events. Safety was assessed in all patients who had received study drug. This trial is registered at ClinicalTrials.gov, number NCT01494506 . Findings: Between Jan 11, 2012, and Sept 11, 2013, 417 patients were randomly assigned either nanoliposomal irinotecan plus fluorouracil and folinic acid (n=117), nanoliposomal irinotecan monotherapy (n=151), or fluorouracil and folinic acid (n=149). After 313 events, median overall survival in patients assigned nanoliposomal irinotecan plus fluorouracil and folinic acid was 6·1 months (95% CI 4·8–8·9) vs 4·2 months (3·3–5·3) with fluorouracil and folinic acid (hazard ratio 0·67, 95% CI 0·49–0·92; p=0·012). Median overall survival did not differ between patients assigned nanoliposomal irinotecan monotherapy and those allocated fluorouracil and folinic acid (4·9 months [4·2–5·6] vs 4·2 months [3·6–4·9]; 0·99, 0·77–1·28; p=0·94). The grade 3 or 4 adverse events that occurred most frequently in the 117 patients assigned nanoliposomal irinotecan plus fluorouracil and folinic acid were neutropenia (32 [27%]), diarrhoea (15 [13%]), vomiting (13 [11%]), and fatigue (16 [14%]). Interpretation: Nanoliposomal irinotecan in combination with fluorouracil and folinic acid extends survival with a manageable safety profile in patients with metastatic pancreatic ductal adenocarcinoma who previously received gemcitabine-based therapy. This agent represents a new treatment option for this population. Funding: Merrimack Pharmaceuticals.